2012
DOI: 10.1021/ml200245t
|View full text |Cite
|
Sign up to set email alerts
|

Negamycin Analogue with Readthrough-Promoting Activity as a Potential Drug Candidate for Duchenne Muscular Dystrophy

Abstract: A series of (+)-negamycin 1 analogues were synthesized, and their readthrough-promoting activity was evaluated for nonsense mutations in Duchenne muscular dystrophy (DMD). A structure-activity relationship study indicated that 11b was the most potent drug candidate. Immunohistochemical analyses suggested that treatment with 11b restored dystrophin expression in mdx mice, a DMD mouse model. Furthermore, 11b decreased serum creatine kinase (CK) levels, an indicator of muscle fiber destruction. Most importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Some examples of bioactive and derivative compounds are shown in Figure 1: (−)-sedamine (Figure 1A), used for the treatment of cognitive disorders, 16 the antidepressant drug fluoxetine (Figure 1B), 17 and (+)-negamycin (Figure 1C), which are used for the treatment of muscular dystrophy. 18 Theoretical and experimental studies have reported on IHBs in 1,3-disubstituted acyclic amino alcohols. However, most of these studies are carried out either only in the gas phase or in a single solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of bioactive and derivative compounds are shown in Figure 1: (−)-sedamine (Figure 1A), used for the treatment of cognitive disorders, 16 the antidepressant drug fluoxetine (Figure 1B), 17 and (+)-negamycin (Figure 1C), which are used for the treatment of muscular dystrophy. 18 Theoretical and experimental studies have reported on IHBs in 1,3-disubstituted acyclic amino alcohols. However, most of these studies are carried out either only in the gas phase or in a single solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The putative miscoding activity of NEG has made it an appealing candidate for the treatment of human genetic disorders caused by nonsense mutations. NEG or its synthetic analogs have demonstrated promising activity in stimulating premature stop codon bypass and partially restoring expression of several disease-related genes inactivated by nonsense mutations (Allamand et al, 2008; Arakawa et al, 2003; Floquet et al, 2011; Taguchi et al, 2012). These findings have made the need to uncover the site and the mode of action of NEG even more compelling.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, structurally designed aminoglycosides with reduced nephrotoxicity and ototoxicity that maintain readthrough activity have been developed ( Shulman et al., 2014 ; Xue et al., 2014 ). In addition, non-aminoglycoside PTC readthrough compounds have been identified by high-throughput library screening ( Du et al., 2009 ; Kayali et al., 2012 ), and some have been chemically modified to improve activity ( Hamada et al., 2019 ; Taguchi et al., 2012 , 2017 ). In addition, several compounds have been found to enhance the activity of PTC readthrough compounds, allowing the use of reduced doses of aminoglycosides and thus reduced toxicity ( Baradaran-Heravi et al., 2016 ; Ferguson et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%